"Bigamists" in Bologna, 1350–1500. (January 2023) - Dean, Trevor
Bigamy trials in medieval secular courts were rare and rarely documented. Where they do survive, they raise interesting questions about the relation between penal law and social practice, about knowledge of church laws on the legitimate forms and processes of marriage, and about gendered aspects of how this crime was perceived, prosecuted and punished. The incomparable riches of the criminal court in Bologna supply a set of nearly thirty cases in the period 1350–1500 which allow these questions to be investigated.